2014
DOI: 10.1371/journal.pone.0085211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wild-Type Shigella Species and Attenuated Shigella Vaccine Candidates on Small Intestinal Barrier Function, Antigen Trafficking, and Cytokine Release

Abstract: Bacterial dysentery due to Shigella species is a major cause of morbidity and mortality worldwide. The pathogenesis of Shigella is based on the bacteria's ability to invade and replicate within the colonic epithelium, resulting in severe intestinal inflammatory response and epithelial destruction. Although the mechanisms of pathogenesis of Shigella in the colon have been extensively studied, little is known on the effect of wild-type Shigella on the small intestine and the role of the host response in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
2
8
0
3
Order By: Relevance
“…Although one has to acknowledge that the Caco-2 cell line may not recapitulate all functions of normal intestinal epithelial cells, their pattern of cytokines following exposure to S. flexneri was consistent with that of other cell lines and that found in vivo (41,42). The availability of polyreactive IgA and IgM Abs with well characterized biochemical properties (29) allowed us to directly address their modes of action in the absence of any other cellular and molecular partners involved in clearance of S. flexneri, therefore allowing a comparison of their respective functional characteristics.…”
Section: Discussionsupporting
confidence: 56%
“…Although one has to acknowledge that the Caco-2 cell line may not recapitulate all functions of normal intestinal epithelial cells, their pattern of cytokines following exposure to S. flexneri was consistent with that of other cell lines and that found in vivo (41,42). The availability of polyreactive IgA and IgM Abs with well characterized biochemical properties (29) allowed us to directly address their modes of action in the absence of any other cellular and molecular partners involved in clearance of S. flexneri, therefore allowing a comparison of their respective functional characteristics.…”
Section: Discussionsupporting
confidence: 56%
“…It appears from various studies that occludin could be a regulator of TJs, rather than an essential component, an interpretation that could explain the absence of intestinal barrier defects in unstressed occludin-deficient mice (France & Turner, 2017). Previous studies have also reported that levels of high-and low-MW occludin differing in phosphorylation levels could change in response to infection by enteric pathogens (Beau, Cotte-Laffitte, Amsellem, & Servin, 2007;Fiorentino, Levine, Sztein, & Fasano, 2014). However, the levels of high-MW form of the occludin in the detergent-insoluble fraction representing hyperphosphorylated occludin appeared to be unaltered in response to CP infection.…”
Section: Discussionmentioning
confidence: 99%
“…4.11 | Immunoblotting of occludin in Triton X-100 soluble and insoluble fractions Triton X-100 soluble and insoluble fractions were prepared as described previously (Fiorentino et al, 2014). Briefly, monolayers were harvested on ice in lysis buffer (1% Triton X-100, 100 mM NaCl, 10 mM HEPES, 2 mM EDTA, 4 mM Na 3 VO 4 , 40 mM NaF and a protease inhibitor cocktail [Complete Mini, Roche Molecular Biochemicals, Mannheim, Germany] and phosphatase inhibitors [Sigma]).…”
Section: Hande Staining and Determination Of Mpo Activitymentioning
confidence: 99%
“…In accordance, Salmonella typhi and Shigella infections lead to claudin-1, ZO-1 and occludin redistribution, occludin phosphorylation and disengagement from the TJ complex. 38,39 Also, Yersinia enterocolitica induces epithelial barrier dysfunction through regional TJ changes. 40 These findings suggest that TJ proteins are frequent targets of intestinal pathogens in the process of invasion and infection.…”
Section: Discussionmentioning
confidence: 99%